Citrabilāsa : Daśama Guru Govinda Siṃha ke darabārī kavi Amrtarāya dvārā racita - Amṛtarāya, poet (Svastika Sāhitya Sadana, 1978)
Riti verse work by the court poet of Govinda Siṃha, 10th Guru of the Sikhs; includes introduction.